PERLINDUNGAN HAK ASASI MANUSIA TERHADAP APARAT KEPOLISIAN BERKAITAN PELAKSANAAN PENGAMANAN UNJUK RASA DALAM PERSPEKTIF UU NO. 39 TAHUN 1999 - Gadis Dinda Firsty Dewi (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACT Human Rights is very essential for Indonesian. Its existence without any discrimination to every human is highly appreciated as refers to Legislation in force in accordance to Law No. 39 of 1999 on Human Rights. Indonesia has law enforcement agency namely the Police who is responsible to maintain security and order of the community.One of the human rights for every human being is voicing their opinion either in public or not. And Indonesia consists of communities that are quite critical and often do demonstration because of disagreement with the existing policies. The out of control actions of protesters resulted in clashes with the Police who secure the demonstration.Keywords: Human Rights, Police, Demonstration.